Study on Cranial and Caudal Mesenteric Arteries in Opossum (Didelphis albiventris) - de Carvalho Pinto e Silva, Jose Ricardo [UNESP]; Fernandes Boaro Martins, Marcia Regina [UNESP]; Guazzelli Filho, Joffre [UNESP] (Soc Chilena Anatomia, 2008)
The objective of this study is to describe the cranial and caudal mesenteric arteries in 10 opossuns after Neoprene latex injection. The cranial mesenteric artery arises from the abdominal aorta, caudally to the celiac trunk, originating the caudal duodenal pancreatic artery, middle and right colic, jejunal and ileocecocolic arteries. The caudal mesenteric artery arises from the aorta, cranially to the external iliac arteries, originating the cranial rectal and left colic arteries.
Keywords: Anatomy; Opossum; Mesenteric arteries